2019
DOI: 10.1038/s41598-019-39884-x
|View full text |Cite
|
Sign up to set email alerts
|

L1cam-mediated developmental processes of the nervous system are differentially regulated by proteolytic processing

Abstract: Normal brain development depends on tight temporal and spatial regulation of connections between cells. Mutations in L1cam, a member of the immunoglobulin (Ig) superfamily that mediate cell-cell contacts through homo- and heterophilic interactions, are associated with several developmental abnormalities of the nervous system, including mental retardation, limb spasticity, hydrocephalus, and corpus callosum aplasia. L1cam has been reported to be shed from the cell surface, but the significance of this during di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 50 publications
2
36
0
1
Order By: Relevance
“…1B). Similar metalloprotease cleavage sites have been reported in vertebrate L1CAM proteins (Beer et al, 1999;Gutwein et al, 2003;Haspel and Grumet, 2003;Jafari et al, 2010;Kalus et al, 2003;Kiefel et al, 2012;Linneberg et al, 2019;Maretzky et al, 2005;Maten et al, 2019;Matsumoto-Miyai et al, 2003;Mechtersheimer et al, 2001;Naus et al, 2004;Nayeem et al, 1999;Riedle et al, 2009;Sadoul et al, 1988;Schafer and Altevogt, 2010;Tatti et al, 2015;Xu et al, 2003;Zhou et al, 2012). Finally, a 40 kDa band is detected in the wild type, but is absent in the controls ( Fig.…”
Section: Results Molecular Analysis Of Previous Sax-7 Mutant Allelessupporting
confidence: 80%
See 1 more Smart Citation
“…1B). Similar metalloprotease cleavage sites have been reported in vertebrate L1CAM proteins (Beer et al, 1999;Gutwein et al, 2003;Haspel and Grumet, 2003;Jafari et al, 2010;Kalus et al, 2003;Kiefel et al, 2012;Linneberg et al, 2019;Maretzky et al, 2005;Maten et al, 2019;Matsumoto-Miyai et al, 2003;Mechtersheimer et al, 2001;Naus et al, 2004;Nayeem et al, 1999;Riedle et al, 2009;Sadoul et al, 1988;Schafer and Altevogt, 2010;Tatti et al, 2015;Xu et al, 2003;Zhou et al, 2012). Finally, a 40 kDa band is detected in the wild type, but is absent in the controls ( Fig.…”
Section: Results Molecular Analysis Of Previous Sax-7 Mutant Allelessupporting
confidence: 80%
“…5B,C), indicating that the cleavage is not essential for function in maintenance of neural architecture, at least with a highly expressed transgene. Consistent with this, motor neuron axon outgrowth defects upon knockdown of l1camb in zebrafish can be rescued by expression of a non-cleavable form of L1cam (Linneberg et al, 2019). However, this may be context-specific as Reelin-mediated cleavage of L1CAM in the mouse brain is important for neurodevelopment (Lutz et al, 2017).…”
Section: Sax-7s Is Robustly Expressed Across the Nervous Systemmentioning
confidence: 61%
“…Yu et al revealed that l1.1, the ortholog of mammalian L1CAM, contributes to spinal cord regeneration in adult zebrafish (Chen et al, 2016). Recently, it has been shown that knockdown experiments of l1.1 lead to hydrocephalus, defects in axonal outgrowth, and myelination abnormalities (Linneberg et al, 2019). These phenotypes have been previously associated with the L1 syndrome.…”
Section: X-linked Formsmentioning
confidence: 99%
“…For example, up-regulation in L1CAM, a member of the Immunoglobulin superfamily, is observed 24 h post BafA1/Rapa treatment; this specific target is regulated by fibronectin domains (which also are overexpressed in the presence of BafA1 treatment at 24 h ( Table 2)). Disruption of FN results in not only the obstruction of protein trafficking but also a plethora of mental disorders such as mental retardation, limb spasticity, and hydrocephalus [32,33]. Other protein dysregulations included the up-regulation of MGF-E8, EPH-B2, and FGF1 and down-regulation of THBS2 and PCSK9 (Figure 2a).…”
Section: Implications Of Bafa1/rapa-dysregulated Intracellular Astrocmentioning
confidence: 99%